DISPARITAS PENJATUHAN PIDANA TAMBAHAN DALAM PERKARA TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA (Studi kasus putusan PN Mamuju Nomor: 3/ Pid-Sus-TPK/2021/PN. Mam. dan putusan PN Bandung Nomor: 55/ Pid-Sus-TPK/2021/PN. Bdg) - Hans Poliman; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
Indonesia is one of the countries that guarantees justice for everyone. In practice, justice and legal certainty as laid out in the foundation of our country is only a sweet writing that has not been properly applied.